The variant c.274A>G (p.Asn92Asp) in KRT17 in a patient with pachyonychia congenita and a novel clinical feature of acne inversa - Wang, Huaiyu; Zhu, Changhua; Dong, Linxin; Wu, Baofeng; Liu, Jingjing; Lin, Lihang; Lin, Daoyao; Chen, Xiangqi; Xiao, Xuemin (Frontiers in Genetics, 2024)
The occurrence of pachyonychia congenita (PC) and acne inversa (AI) may be related to gene mutations. The aim of this study is to identify the genetic cause in a patient with PC and AI, and to explore the possible molecular mechanism of their co-occurrence. The clinical data of the proband were collected, and the genomic DNA of the proband and unaffected parents were extracted. The variant sites of the proband were identified by whole-exome sequencing, and then the variant sites of the proband and his parents were verified by Sanger sequencing. A heterozygous variant in KRT17 gene was found in the patient, resulting in a missense amino acid variant (p.N92D). The variant was not found in his parents or 100 unrelated healthy controls. In addition, this variant was not found in the gnomad v4 database. The three-dimensional structure analysis of the protein suggested that the polarity of amino acids changed after the variant. After lentiviral plasmid transfection into HaCaT cells, the expression level of NOTCH signaling decreased in the constructed c.274A>G (p.Asn92Asp) of KRT-17 mutant cells compared to that in the wild-type. Subsequent verification confirmed that differences in the expression levels of p-PI3K, AKT and p-AKT between the groups were not statistically significant. Although this variant has been reported previously, our findings could expand the spectrum of co-occurrence of PC and AI with KRT17 gene variants, and elucidated the possible pathogenesis at the protein level, thereby laying a foundation for the genetic diagnosis and genetic counseling provided to individuals with PC.